WORKFORCE MARKET RESEARCH: THE CASE OF ŠIAULIAI REGION - Šalkauskienė, Ligita; Pocevičienė, Rasa (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The workforce market is rapidly changing technologically, complex today’s economics restructuring and requirements to the labor market are transforming. The issue of matching workforce market supply and demand from a requirements occupational perspective is becoming more important than ever. Workforce is a core value of a company. It is very important to analyze and predict what qualifications will need professionals to have in order to successfully participation in the labor market. This area of research is one of the components that ensure the quality of educational teaching. Quality is ensured by developing appropriate study programs that are in line with current / future labor market challenges. Depending on the projected demand of the labor market, study programs can be oriented towards specialization. The article presents the workforce market research on the example of Siauliai region. Keywords: workforce, labor market, demand, supply, human resources.